ANALISIS METADATA PADA LITERATUR PEMASARAN DAN BLOCKCHAIN - Karunia, Erick; Nursia, Nursia; Suryaningsih, Suryaningsih; Azis, Muh. Irfandy (Gapenas Publisher, 2024)
This study explores the integration of metadata in marketing and blockchain technology, offering innovative solutions to address challenges in metadata management, such as the lack of standardization, security, and data privacy. Using a descriptive-qualitative approach, the research analyzes literature related to marketing metadata and the potential application of blockchain to enhance efficiency and transparency. Data were collected through a systematic literature review encompassing various academic journals and conference proceedings and analyzed using descriptive statistical techniques and data visualization. The findings indicate that blockchain, through its features of transparency, immutability, and smart contracts, can improve metadata integrity and facilitate data-driven decision-making. The study also identifies a significant increase in related literature since 2020, with major contributions from academic institutions in India, the United States, and China. The results address a gap in the literature by proposing an integrative framework for applying blockchain in marketing metadata management. Theoretically, this research provides a novel foundation for understanding the intersection of marketing metadata and blockchain. Practically, the findings offer guidance for companies to enhance data efficiency and security through blockchain adoption. Policy implications emphasize the need for regulatory development to support ethical and legally compliant blockchain adoption in alignment with data privacy laws. This study paves the way for further empirical research and interdisciplinary approaches to optimize the application of this technology in digital marketing.